Grammar practice for intermediate students : with answers - Walker, Elaine; Elsworth, Steve; Nguyễn Văn Phước; Ban biên dịch First News. (Tp.HCM : Nxb Trẻ, 2003)
This book sets out all the main areas of English grammar and gives clear explanations of grammar points, followed by practice exercises.
Includes index.
Keywords: English language; Grammar; English language -- Grammar